Oxygenation targets for endovascular therapy in acute ischemic stroke patients (Oxy-TARGET): protocol for a single-centre, open-label randomised controlled trial - Anxin Wang; Zhengfang Hu; Ruquan Han; Fa Liang; Youxuan Wu; Minyu Jian; Xinyan Wang; Yunzhen Wang; Haiyang Liu; Xuan Hou; Kangda Zhang; Zihui Zhang (BMJ Open)
Introduction Preclinical studies have shown that oxygen therapy can improve ischaemic brain tissue oxygen tension, reduce reperfusion injury after revascularisation, promote neuroregeneration and inhibit inflammatory responses potentially exerting a beneficial effect after endovascular treatment (EVT) in patients with acute ischaemic stroke (AIS). However, the optimal fraction of inspired oxygen (FiO2) during EVT under general anaesthesia is currently unknown. Therefore, we are conducting a randomised controlled trial (RCT) to evaluate the impact of high-concentration oxygen vs low-concentration normobaric oxygen on early neurological function after EVT.Methods and analysis The Oxy-TARGET trial is an ongoing prospective, open-label, parallel-design RCT being conducted at Beijing Tiantan Hospital, Capital Medical University. It aims to enrol 200 anterior circulation AIS patients undergoing EVT under general anaesthesia between February 2024 and December 2026. Eligible participants are randomly assigned at a 1:1 ratio to receive FiO2=80% or FiO2=30% through endotracheal intubation, with the gas flow rate set at 4 L/min. The inspiratory oxygen concentration at the tracheal intubation site (delivered FiO2) was recorded concurrently. The primary outcome is the incidence of early neurological improvement (a National Institutes of Health Stroke Scale (NIHSS) score<10 points at 24±2 hours after EVT). Additional safety and efficacy parameters included the 24-hour ΔNIHSS (baseline NIHSS - NIHSS at 24-hour) score, final infarct volume at 72 hours postrandomisation, 90-day Modified Rankin Scale (mRS) score, early neurological deterioration, postoperative pulmonary complications, blood gas parameters, symptomatic intracranial haemorrhage and 90-day mortality.Ethics and dissemination Following a rigorous review process, Oxy-TARGET has received official approval from the Ethics Committee of Beijing Tiantan Hospital, Capital Medical University (KY2023-257-02). The standardised research protocol adopted in this trial is designed to enhance anaesthesiologists’ understanding of respiratory management for AIS patients during EVT. The findings of this study are intended to be disseminated through publications in international peer-reviewed journals, presentations at national and international academic conferences and broad distribution via online platforms.Trial registration number NCT06224426.